Impact of European Food Safety Border Inspections on Agri-Food Exports: Evidence from Chinese Firms - Matthias Beestermöller; Anne-Célia Disdier; Lionel Gérard Fontagné (Center for Economic Studies and ifo Institute (CESifo), 2016)
The cost of complying with a sanitary standard is certain. However, such regulatory measure is a source of uncertainty for exporting firms in relation to border rejections. Shipments may fail to pass inspections and may be refused entry into the importing country. We examine how the risk of rejection at European borders is affecting Chinese agri-food exporters. We combine information on rejections with Chinese firm-level export data. Border rejections amplify the turnover among firms at the extensive margin of trade. This risk is curbing small exporters and resulting in a concentration of Chinese exports from big and more productive exporters.
Keywords: F14; L25; Q17; Q18; 330; food safety; border inspections; import refusals; uncertainty; firm heterogeneity